EVALUATION OF THERMAL CONDITIONS AND STANDARDS, A CASE OF SCHOOL BUILDINGS IN ORANGI TOWN, KARACHI - Fabiha Khalid; Hira Qureshi; Samar Shamim Hussain (Spectrum of Engineering Sciences, 2025)
The rapid global urbanization has led to significant climatic changes, with rising temperatures being a pervasive concern across various regions. In Karachi, these shifts have particularly impacted the thermal comfort within built environments. As a result, occupants increasingly spend more time indoors to mitigate extreme weather conditions. In educational settings, where students spend a large portion of their day, the thermal environment plays a crucial role in both their comfort and learning efficiency. There is well-established evidence linking indoor environmental conditions to student performance, highlighting the importance of a suitable thermal environment for fostering optimal learning outcomes. Considering this, it is critical to establish a satisfactory indoor environment in educational buildings. This study focuses on private school buildings in Orangi Town, Karachi, which are constructed on small plots. These schools have thermal environments that are not conducive to effective learning. The poor thermal conditions have adversely affected the behavior and productivity of building occupants, particularly students. Therefore, this research aims to assess the thermal conditions and various building-related factors that contribute to the discomfort. The methodology for this study includes mapping, field surveys, and quantitative measurements of indoor and outdoor temperatures and humidity levels from December 2023 to May 2024. Additionally, the study will use an adaptive model to identify comfort temperature standards for the surveyed school buildings and provide recommendations for creating a more comfortable and productive learning environment.